Membongkar Dampak Cyberbullying: Perspektif Guru Bk Dalam Menangani Kasus di Sekolah - Melindra Jiyestha; Aninda Ramadina Andhika; Sabrina Sabrina; William Djorghi; Zen Mahendra; Agung Tesa Gumilar (International Forum of Researchers and Lecturers, 2025)
Cyberbullying is a major challenge for students in the digital age, with impacts that include their mental health, academic achievement, and social interactions. Guidance and Counseling (BK) teachers have an important role in handling this case, but still face various obstacles, including lack of understanding and minimal special training. This study explores the perspectives of BK teachers in dealing with cyberbullying and the strategies used to overcome these challenges. Findings suggest that effective interventions require a comprehensive approach involving schools, families, and communities. Digital ethics education, stricter school policies, and peer support have been shown to help prevent and address cyberbullying. Therefore, strategic steps are needed to strengthen the role of BK teachers and create a safer school environment for students.